Modulation and Multiple Access for Beyond 6G Electromagnetic Nanonetworks in the Terahertz Band - Pankaj Singh; Sung-Yoon Jung (IEEE Access)
The advent of groundbreaking nanomaterials like graphene, renowned for their exceptional electrical properties, has ignited significant interest in nanocommunication. The potential to develop graphene-based plasmonic nanoantenna arrays and transceivers, combined with the capability of transmitting nanocommunication pulses at terahertz (THz) frequencies—bridging the THz gap in the electromagnetic spectrum—has been particularly compelling. Over the past decade, research in nanocommunication has led to remarkable advancements, particularly in the physical and link layers. These developments have paved the way for integrating fully operational nanonetworks into beyond 6G (B6G) wireless systems. Given the anticipated data rates in the terabits per second range for nanonetwork applications, continuous efforts are being made to develop new modulation and multiple access (MA) schemes. This survey paper explores the most advanced modulation and MA strategies tailored for B6G nanosystems operating in the THz band. Unlike previous surveys, our focus is on the physical layer, emphasizing rate-division and time-hopping strategies, including pulse position and pulse amplitude modulation techniques. We begin with an introduction to the foundational aspects of nanocommunication as an integral part of B6G nanosystems, followed by a detailed examination of various modulation schemes and their applicability to MA in nanonetworks. The paper concludes with a comparative analysis of these approaches regarding link capacity and a discussion of key open issues and future research directions for the design of electromagnetic nanocommunication systems.